ANALISIS PEMBANGUNAN PRASARANA ANGKUTAN DAN EKSTRAKsl KAYU SERTA DAMPAKNYA. TERHADAP LINGKUNGAN HUTAN DI PROPINSI RIAU - Djaban tinambunan (Jurnal Penelitian Hasil Hutan, 1991)
An investigation on various aspects of timber harvesting practicues in two loggini companies in Riau has been  conducud in June 1991. One of them is operating in dry  land forests  and the other is in swamp forests.Road construction in the first  company is accomplished by the steps of selecting route Iocation, land clearing and road forming, road grading, and right of way clearing with the total cost of Rp. 3.8 million/km. Whereas, log extraction is done by the steps of felling, skidding, debarking, loading, hauling and unloading with the total cost of Rp. 8,210/cu.m.In swamp forests,  rail  road construction follows the steps of route survey, right of way clearing, installing rall suppors and steel rails with the cost of Rp. 8,420,000/km, including the costs of logs used for the supports amountr to 151  cu.m/km and steel rails. By using this facility and manual (kuda-kuda) skidding, it is found that the cost of log extraction  is Rp. 13,250/cu.m.Logging roads have many land openings and steep, bare soils so that they are in the condition of high soil erosion potential. Whereas, for rail roads, it is noticed that their soil erosion is low because the land on both sides and under  the rails is well covered by litter,  logs  and vegelation roots.